2009
DOI: 10.1111/j.1475-097x.2009.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Rowing, the ultimate challenge to the human body – implications for physiological variables

Abstract: Clinical diagnoses depend on a variety of physiological variables but the full range of these variables is seldom known. With the load placed on the human body during competitive rowing, the physiological range for several variables is illustrated. The extreme work produced during rowing is explained by the seated position and the associated ability to increase venous return and, thus, cardiac output. This review highlights experimental work on Olympic rowing that presents a unique challenge to the human capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…The strong positive correlation between baseline muscle carnosine content and the speed during four different rowing distances (Table 1) suggests that besides the known performance-related factors [anaerobic threshold (30), absolute maximum oxygen uptake (V O 2max ) (9,31,45), muscle composition (18,29), and anthropometric profile (10)], muscle carnosine content is also a determinant of rowing performance.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The strong positive correlation between baseline muscle carnosine content and the speed during four different rowing distances (Table 1) suggests that besides the known performance-related factors [anaerobic threshold (30), absolute maximum oxygen uptake (V O 2max ) (9,31,45), muscle composition (18,29), and anthropometric profile (10)], muscle carnosine content is also a determinant of rowing performance.…”
Section: Discussionmentioning
confidence: 93%
“…In this context, rowing is an ideal model to study, because the official race distance (2,000 m) takes about 5.5-8 min depending on sex, category, boat type, and environmental conditions. A 2,000-m rowing race has a specific profile, in which anaerobic alactic and lactic, as well as aerobic capacities are stressed to their maximum (45). According to Körner and Schwanitz (27), a 2,000-m rowing race can be divided into three main phases, which are time bound and hence distance bound.…”
mentioning
confidence: 99%
“…While the physiological and biomechanical parameters associated with rowing performance have been largely studied (Hagerman 1984;Soper and Hume 2004;Volianitis and Secher 2009), few data are available about muscle coordination [defined as ''a distribution of muscle activation or force among individual muscles to produce a given combination of joint moments'' (Prilutsky 2000)]. Using surface electromyography (EMG), some studies have reported muscle activity patterns on a rowing ergometer (Lay et al 2002;Pollock et al 2009;Rodriguez et al 1990;Wilson et al 1988).…”
Section: Introductionmentioning
confidence: 98%
“…Accordingly, Olympic rowing is a type of whole body exercise that is considered to present the extreme challenge to homeostasis (Volianitis and Secher 2009). Yet, it is not known to what extent intracellular acidosis is reflected in the observed intravascular acidosis.…”
Section: Introductionmentioning
confidence: 99%